Mitigation in the law of damages - Dyson, A (2016)
This thesis is the first monograph on mitigation in the English law of damages. Mitigation concerns the effect of the claimant's post-breach conduct on the assessment of damages. The leading texts propose that the doctrine consists of two main rules: first, the claimant cannot recover damages for losses that it could reasonably have avoided (the 'avoidable loss rule'); and second, the claimant cannot recover damages for losses that it has in fact avoided, except where the benefit did not 'arise out of the breach' (the 'avoided loss rule'). This thesis proposes a new descriptive and explanatory account of mitigation. It argues that the apparent distinction between the avoidable and avoided loss rules is illusory; instead, the rules of mitigation apply symmetrically to both harms and benefits. Contrary to the leading texts, it is argued that judges have been correct to explain mitigation as an aspect of causation. However, to understand why, we must move beyond the 'but-for' concept of causation and instead seek to apply the ordinary causal principles that people use outside the law. The implications of the thesis extend beyond the law of mitigation. First, the rules of mitigation also explain the so-called 'market rule', the 'betterment' rule, and 'supervening acts by the claimant'. Second, the thesis shows why the rights-based model of damages has overstretched in claiming that the law provides a universal entitlement to 'substitutive damages' for the infringement of rights. Third, the thesis revives and defends key arguments from Hart and Honoré's seminal investigation into ordinary causal concepts, with implications for every area of law where causal reasoning is invoked. Author also known as Andrew Summers